Effect of capacitation of stallion sperm with polyvinylalcohol or bovine serum albumin on penetration of bovine zona-free or partially zona-removed equine oocytes - Choi, Y. H.; Landim-Alvarenga, F. C. [UNESP]; Seidel, G. E.; Squires, E. L. (My University, 2003)
Experiments were conducted to study effects of macromolecules on stallion sperm capacitation and fertilization as determined by penetration of bovine zona-free and equine partially zona-removed oocytes. Stallion sperm were capacitated in TYH medium (modified Krebs-Ringer bicarbonate) supplemented with either 1 mg/mL of polyvinylalcohol (PVA) or 4 mg/ mL of BSA. Capacitation was induced with 8 bromoadenosine cyclic monophosphate (8BrcAMP; 0.5 mM) alone or in combination with 0.1 μM of ionomycin. Intraspecies gametes were co-incubated in TYH/PVA or TYH/ BSA for 18 to 20 h. For zona-free bovine oocytes, penetration rate (35%) with the combination of 8BrcAMP and ionomycin in PVA-containing medium was higher (P < 0.05) than any treatment in BSA-containing medium (5 to 6%). A similar study was conducted using equine oocytes with partially removed zonae. Sperm capacitated and used for in vitro fertilization (IVF) in PVA-containing medium had higher penetration rates (P < 0.01) than sperm in BSA-containing medium (54 vs. 11%). The effect of equine preovulatory follicular fluid on bovine oocyte penetration was assessed. Bovine oocytes were matured in tissue culture medium-199 with 0, 20, 50, or 100% equine preovulatory follicular fluid, and 1 IU/mL of equine chorionic gonadotropin. Stallion sperm were treated with 8BrcAMP + ionomycin in PVA- or BSA-containing media. The penetration rates of bovine zona-free oocytes by stallion sperm were again higher with PVA (47%) than BSA (18%; P < 0.01). Penetration rates of oocytes matured in 100% follicular fluid were higher (P < 0.05) than for oocytes matured with 0% follicular fluid. The effects of equine follicular fluid and PVA/BSA during sperm capacitation on standard bovine IVF were examined. Culture of bovine oocytes with equine follicular fluid did not affect oocyte maturation or penetration rates after IVF. Bovine sperm capacitated with heparin in PVA-containing medium yielded lower (P < 0.05) fertilization rates than those capacitated in BSA-containing medium when incubated with both zona-intact and zona-free bovine oocytes. In summary, PVA was superior to BSA for ionophore-induced capacitation of equine sperm for penetration of zona-free bovine oocytes or partially zona-removed equine oocytes, but not for standard bovine IVF with bovine sperm. Zona-free bovine oocytes may be useful for assaying in vitro capacitation and fertilization of stallion sperm. © 2003 American Society of Animal Science. All rights reserved.
Keywords: Bovine Serum Albumin; Capacitation; Follicular Fluid; Oocytes; Spermatozoa; Stallion; Bovinae; Equidae; Potato virus A; 8 bromo cyclic AMP; bovine serum albumin; polyvinyl alcohol; animal; animal disease; cattle; culture technique; drug effect; female; fertility; fertilization in vitro; horse; male; oocyte; ovary follicle fluid; physiology; spermatozoon capacitation; zona pellucida; 8-Bromo Cyclic Adenosine Monophosphate; Animals; Cattle; Culture Techniques; Female; Fertilization in Vitro; Horses; Male; Polyvinyl Alcohol; Serum Albumin, Bovine; Sperm Capacitation; Sperm-Ovum Interactions; Zona Pellucida